2017
DOI: 10.3389/fonc.2017.00194
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and Lung Cancer: A Geo-Regional Perspective

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) represents the most frequently diagnosed subtype of this morbid malignancy. NSCLC is causally linked to tobacco consumption with more than 500 million smokers worldwide at high risk for this fatal malignancy. We are currently lagging in our knowledge of the early molecular (e.g., genomic) effects of smoking in NSCLC pathogenesis that would constitute ideal markers for early detection. This limitation is furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 84 publications
2
51
0
Order By: Relevance
“…It is worthwhile to mention that there are few molecular alterations that have been described in premalignant phases of lung cancers, particularly LUADs and LUSCs. However, while physical screening, identification and thus molecular characterization of the earliest premalignant lesions (PMLs) remains hampered by their elusive pathology, understanding their immune biology is gaining momentum as a promising surrogate for the early detection of lung cancers, and as a window of opportunity to intercept their progression using novel immune-based prevention strategies (240). Indeed, successful interventions at premalignant stages were evident across multiple tumors.…”
Section: Rewinding Lung Carcinogenesis: the Antecedents Of Cancer Invmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to mention that there are few molecular alterations that have been described in premalignant phases of lung cancers, particularly LUADs and LUSCs. However, while physical screening, identification and thus molecular characterization of the earliest premalignant lesions (PMLs) remains hampered by their elusive pathology, understanding their immune biology is gaining momentum as a promising surrogate for the early detection of lung cancers, and as a window of opportunity to intercept their progression using novel immune-based prevention strategies (240). Indeed, successful interventions at premalignant stages were evident across multiple tumors.…”
Section: Rewinding Lung Carcinogenesis: the Antecedents Of Cancer Invmentioning
confidence: 99%
“…While animal models provide valuable mechanistic insights which can be validated in pertinent cohorts as a means of biological interpretation of response to therapy, there have been other parallels and precursors besides the elusive PMLs, which, if interpreted with caution, can direct the search for immune-based biomarkers for early detection of lung cancer. One prominent example is COPD, a chronic disease of the lung characterized by inflammation of the epithelial airway and alveoli and driven by the exposure to cigarette smoke (201,240). Several studies have shown a tightly knit association, sometimes causal, between COPD and lung cancer particularly among smokers.…”
Section: Copd Markers As Surrogate Tools For Early Management Of Lungmentioning
confidence: 99%
“…Lung cancer, which can be divided into small cell lung cancer and non-small cell lung cancer (NSCLC), is the leading cause of cancer-related deaths worldwide [1,2]. NSCLC accounts for approximately 85% of lung malignancies [3], and nearly 75% of NSCLC cases are diagnosed in the advanced stage with an estimated 5-year survival rate of 18% in the United States [4].…”
Section: Introductionmentioning
confidence: 99%
“…It causes more deaths per year than other cancers and the mortality has been high for recent decades among both men and women [2] . Non-small cell lung cancer (NSCLC) epitomizes the most frequently diagnosed subtype of this fatal malignancy [3] . Over the past 50 years, NSCLC accounts for 85% to 90% of lung cancer, especially squamous cell carcinoma (SCC) and adenocarcinoma (ADC) [4] .…”
Section: Introductionmentioning
confidence: 99%